Field wind erosion measurements with Big Spring Number Eight (BSNE) and Modified Wilson and Cook (MWAC) samplers - Mendez, Mariano Javier (2011)
The aim of this study was to compare the horizontal mass flux (HMF) of Aeolian sediment obtained from field wind erosion measurements with the Modified Wilson and Cook (MWAC) and Big Spring Number Eight (BSNE) and to analyze the effectiveness of exponential, power, logarithmic and rational equations to calculate the horizontal mass transport (HMT) for each sampler type. With this purpose wind erosion was measured on fine sandy loam soil in 10 erosion events between December 4, 2008 and July 1, 2009. The relative efficiency of the MWAC related to BSNE (REW/B, quotient between the HMF of MWAC and the HMF of BSNE multiplied by 100) was 247% while REW/B obtained from the absolute efficiency of the BSNE (85% to 95%) and MWAC (44% to 120%) found in previous studies, was between 51% and 141%. The REW/B increased with height, as a consequence of the wind speed increase and particle size decrease, which reduces the efficiency of the BSNE while the efficiency of the MWAC remains constant. Depending on the equation used, the HMT of MWAC was from 2.1 to 2.53 times higher than the HMT of BSNE indicating that if the HMF is corrected by the REW/B, found in this study, the HMT obtained with the MWAC and BSNE is similar. The HMT obtained from exponential equations was 16% higher than the power equation and, 62% and 11% lower than logarithmic and rational equations respectively. In spite of this, the HMT obtained with different equations presented a good relationship with each other (p<0.05), indicating that the HMT can be corrected and compared between equations. This study shows that the HMF and HMT data obtained from field measurements with the BSNE and MWAC are different. Nevertheless, comparable measurements of wind erosion can be obtained with both samplers taking into account the relative efficiency and the relationship between equations found in this study. © 2011 Elsevier B.V.